Techno-economic feasibility assessment and performance analysis of standalone solar photo voltaic-biomass hybrid system with optimized storage: a case study—Grand Bassa, Liberia - White, Jackson G.; Samikannu, Ravi; Oladiran, Moses Tunde; Yahya, Abid; Makepe, Patricia; Gamariel, Gladys; Ladu, Nyagong Santino David; Tlhabologo, Bokang Agripa; Kadarmydeen, Maruliya Begam; Gunasekaran, Kanimozhi; Amuhaya, Lilian (Frontiers in Energy Research, 2024)
Introduction: Liberia has a significant obstacle in terms of restricted power accessibility, as only 26.7% of its populace have access to electrical energy. To tackle this issue, there is a collaborative effort between the government and private sector to undertake energy projects aimed at enhancing the power supply of the grid. The purpose of this study is to evaluate the techno-economic feasibility and analyze the performance of a standalone biomass/solar photovoltaic (PV) hybrid energy system for a rural Liberian community that mostly relies on traditional biomass. Methods: HOMER pro program was used to configure the system, model the community’s load over a year, and generate the resource data of the location. Results and Discussion: Four different configurations were obtained and analyzed both technically and economically to determine the most feasible configuration. This study has shown that a hybrid configuration incorporating Biomass Gasifier, Solar PV, and Battery storage is more feasible with annual output power of 77104 kWh/yr, LCOE (/kwh) of 0.29 and NPC () of 0.3979 million. If implemented with external funding, it will enhance the education, economic and socio-economic status of rural settlements. The results will serve as a valuable resource for informing choices on the implementation of the hybrid energy solution and guaranteeing its sustained efficacy within the community.